Using Biphenyl and Diphenyl Oxide Substances in the Heat Exchange Process in the Oil Industry (Texas Journal of Engineering and Technology, 2022)
Biphenyl and diphenyl oxide substances are organic compounds and they have a variety of applications, including but not limited to dye carriers, food preservatives, raw materials, heat transfer, and chemical synthesis. In this study, a production bank with a 50,000 barrel per day capacity was simulated using the Aspen Hysys program. The mixture of the diphenyl oxide and biphenyl was used as the heat transfer fluid and then entered the closed system heat exchanger in order to increase the oil temperature. Also, the importance of utilizing these substances in heat exchange processes was explained through interpreting the behavior of different parameters (pressure, density, viscosity, entropy, heat flow, actual liquid flow, and thermal conductivity) with temperature. The results were provided in this research in the form of curves, with explanations of the relationships between heat and various properties of a substance. Finally, the mixture of biphenyl and diphenyl oxide has good efficiency in heat exchange processes; consequently, it can be used in the oil industry.